AN APPLLICATION OF MULTIPLE RENEWABLE ENERGY SYSTEMS WITH PLURAL GOAL OPTIMIZATION - Durvasula Sri Rama Sastry; Durvasula Sri Rama Sastry; P.S. Kishore (Utilitas Mathematica, 2025)
The Proposed System is a mixed system with features of renewable nature and hybrid nature. It consists of panels which are photovoltaic in nature (photo voltaic cells), turbines which operates with wind (wind turbines), and also it will have non- stop production of hydrogen through green energy route using reformers. Genetic algorithm is applied for optimization and is validated. In the hypothecated system the storage of hydrogen the annualized cost for storing the hydrogen is minimized and the energy wastage is reduced by 65%. A detailed sensitivity analysis conducted on the effect of cost variation, impact of different kinds of storage, and various capacities on system performance. the issues related to green criteria as environment sustainability has become the need of the hour optimization of cost, and green criteria are taken as objectives in the paper Multi-objective formulation is done, and a suitable metaheuristic is applied to solve the problem.